Numerical modeling of complex radiative heat transfer - N. I. Moskalenko; L. V. Rodionov; M. S. Khamidullina; I. A. Afanasyev (Известия высших учебных заведений: Проблемы энергетики)
The application of numerical simulation of the fine structure of the absorption and emission in the complex problems of radiative heat transfer is consider when the structural characteristics of the environment and the boundary conditions are different strong inhomogeneities in temperature, chemical composition and distribution of the radiation sources. The very nature of radiative heat transfer and temperature variation trends over time are determined by the acute effects of selection of the spectra and their modeling require knowledge of spectral line parameters: intensity, half-width position of the centers, contours. Compared with the use of approximate methods of calculation functions of the spectral transmittance numerical simulation reveals the effects of enlightenment environment or enhancing its absorption as a function of the temperature field. The effect of the temperature shift of centers the spectral lines over to radiation heat transfer in high-temperature environments is noted. Focuses on the study of the function of the spectral transmission as the main characteristics that define the radiative heat transfer.